Efektivitas Manajemen Diare di Tatanan Rumah Tangga dalam Meningkatkan Pengetahuan dan Keterampilan Penanganan Diare Anak - Rahmawati, Eni; Rahayu, Eva; Pratama, Koernia Nanda (Jurusan Keperawatan FIKES UNSOED, 2017)
Diarrhea is a major cause of morbidity and mortality of children under five in developing countries and is one of main cause of malnutrition. Meanwhile, mother's behavior and knowledge about health impact on child’s mortality. Management of diarrhea is a therapeutic treatment by empowering parents, which is focused on the treatment of diarrhea at home. This study was aimd to identify the effect of management of diarrhea on the behavior of parents in caring for of children with diarrhea at home. This research method was the Quasi Eksperiment Pretest-Posttest Design with Control Group. The subjects were 55 respondents selected by purposive sampling. Knowledge and skills were measured in 18 days, using a knowledge questionnaire with 21 questions, while the skills was measured through direct observation. The average score effect on knowledge of the treatment and control group were 37.9 and 6.15. While the average score effect on skills of the treatment and control group were 35.07 and -0.51. The P-value in both variables using Independent Sample t-Test showed was 0.000, which means is a significant difference between the treatment and control groups. The management of diarrhea is effective to improve parents knowledge and skills in the treatment of childhood diarrhea.